Influence Of Triu-B, Ovsynch And Heatsynch Protocols On Estrus Induction Response, Conception And Biochemical And Minerals Profile In Anoestrus Crossbred Cows - Buhecha, K.V.; Dhami, A.J.; Hadiya, K.K.; Parmar, C.P.; Parmar, S.C.; Patel , J.A. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
This study was planned to evaluate the fertility response and plasma profile of biochemical and mineral constituents in 46 postpartum anoestrus crossbred cows (>90 days) treated with different standard hormonal protocols (TriU-B/PRID, Ovsynch and Heatsynch, n=12 each), keeping untreated anoestrus control (n=10) and normal cyclic control (n=10) groups. All the cows (100 %) under TriU B, Ovsynch and Heatsynch protocols exhibited induced estrus within mean intervals of 67.00±1.74, 69.83±0.87 and 68.17±1.24 h, respectively, from PGF2α injection, with prominent to moderate estrus signs. The conception rates obtained at induced estrus in cows under TriU-B, Ovsynch and Heatsynch protocols were 33.33, 41.66 and 33.33 per cent, respectively. The corresponding overall conception rates of three cycles were 50.00, 58.33 and 41.66 per cent, respectively. In anoestrus animals under TriU-B, Ovsynch and Heatsynch protocols, and in normal cyclic control group, the overall pooled mean plasma total cholesterol concentrations found were 218.32±5.81, 218.65±6.04, 202.44 ±5.73 and 225.87±9.09 mg/dl (P<0.05), respectively. The corresponding values for total protein were 7.95±0.06, 7.57 ± 0.05, 7.94 ± 0.14 and 8.69 ± 0.16 g/dl (P<0.05), plasma calcium 9.15 ± 0.06, 9.18 ± 0.09, 10.01 ± 0.08 and 10.15 ± 0.09 mg/dl (P<0.05) and inorganic phosphorus 4.33±0.10, 4.02 ± 016, 5.00 ± 0.18 and 4.90 ± 0.10 mg/dl (P<0.05). The influence of treatment days (0, 7, 9/AI or day 21 post-AI) was not significant for any of the traits in any of the groups, except for protein in Heatsynch protocol. The levels of all four constituents were significantly higher in normal cyclic control group than the values found in most treatment groups, which were at par. The conceived cows had insignificantly higher values of total cholesterol and protein as compared to non-conceived ones in most treatment protocols and even in cyclic control groups. In general, Ovsynch protocol followed by TriU-B appeared the best for induction of estrus and improvement of fertility without influencing the blood biochemical and mineral profiles in anoestrus crossbred cows.